Donor-derived CD19 CAR-T cell therapy of relapse of CD19-positive B-ALL post allotransplant - Zhang, Cheng; Wang, Xiao-Qi; Zhang, Rong-Li; Liu, Fang; Wang, Yi; Yan, Zhi-Ling; Song, Yong-Ping; Yang, Ting; Li, Ping; Wang, Zhen; Ma, Ying-Ying; Gao, Lei; et al. (Leukemia, 2021)
Safety and efficacy of allogeneic anti-CD19 chimeric antigen receptor T cells (CAR-T cells) in persons with CD19-positive B-cell acute lymphoblastic leukemia (B-ALL) relapsing after an allotransplant remain unclear. Forty-three subjects with B-ALL relapsing post allotransplant received CAR-T cells were analyzed. 34 (79%; 95% confidence interval [CI]: 66, 92%) achieved complete histological remission (CR). Cytokine release syndrome (CRS) occurred in 38 (88%; 78, 98%) and was ≥grade-3 in 7. Two subjects died from multiorgan failure and CRS. Nine subjects (21%; 8, 34%) developed ≤grade-2 immune effector cell-associated neurotoxicity syndrome (ICANS). Two subjects developed ≤grade-2 acute graft- versus -host disease (G v HD). 1-year event-free survival (EFS) and survival was 43% (25, 62%). In 32 subjects with a complete histological remission without a second transplant, 1-year cumulative incidence of relapse was 41% (25, 62%) and 1-year EFS and survival, 59% (37, 81%). Therapy of B-ALL subjects relapsing post transplant with donor-derived CAR-T cells is safe and effective but associated with a high rate of CRS. Outcomes seem comparable to those achieved with alternative therapies but data from a randomized trial are lacking.